East African running - Pitsiladis, Y.; Bale, J.; Sharp, C.; Noakes, T. (Routledge, 2007)
In the world of competitive sport, debate surrounding the predictors of success is intense, and the disproportionate success of east African distance runners has generated much theorising. Within the academic community, research is specialised and has been restricted by isolation inside either the natural science or the social science communities. East African Running: Towards a Cross Disciplinary Perspective presents a rare collaboration between leading researchers from both sports sciences and social sciences to offer the fullest yet exploration of the questions raised by the East African running phenomenon. The text covers: - Socio-economic and cultural perspectives, - Physiological perspectives, - Athleticogenomic perspectives. Presenting a uniquely integrated approach, this book is a fascinating resource for students and researchers interested in the sources of success in endurance sport.